Clinical outcomes of second relapsed and refractory first relapsed paediatric AML: A retrospective study within the NOPHO‐DB SHIP consortium. (4th February 2022) - White, Tara; Kaspers, Gertjan; Abrahamsson, Jonas; Arad‐Cohen, Nira; Cianci, Daniela; Fernandez, Jose; Ha, Shau‐Yin; Hasle, Henrik; De Moerloose, Barbara; Zwaan, C. Michel; Goemans, Bianca F.
Summary: As treatments for second relapsed and refractory first relapsed paediatric AML transition from purely palliative to more commonly curative in nature, comparative data is necessary for evaluating the effectiveness of emerging treatment options. Furthermore, little is known about predictors of prognosis following third‐line therapy. From 2004 until 2019, 277 of the 869 patients enrolled in NOPHO‐DB SHIP consortium trials experienced a first relapse and, of these patients, 98 experienced refractory first relapse and 59 a second relapse. Data on patient and disease characteristics within this cohort of 157 patients was analysed to determine probability of overall survival (pOS) and to identify factors influencing survival. Data on early treatment response and complete remission were not available. One and 5‐year pOS were 22 ± 3% and 14 ± 3%, respectively. There was no statistically significant difference in survival between refractory first relapsed and second relapsed AML. Factors influencing prognosis included: late relapse, type of third‐line treatment, FLT3 mutational status, and original treatment protocol. These data provide a baseline for evaluating the effectiveness of emerging therapies for the treatment of children with refractory first relapsed and second relapsed paediatric AML and evidence that select patients receiving third‐line therapy can be cured.